Distintion Principle dalam Hukum Humaniter sebagai Jaminan Penghormatan Terhadap Hak Asasi Manusia dan Perspektifnya Menurut Syari’at Islam - Palupi, Dwi Astuti; Rosra, Deswita (Faculty of Law, Andalas University, 2023)
Human rights violations often occur when war / armed conflict disputes occur that cause damage and destruction, even involving people who are not involved in the war. Humanitarian law has firmly regulated the protection of victims who are not active in the war by applying the